2018
DOI: 10.1093/bib/bby010
|View full text |Cite
|
Sign up to set email alerts
|

Open-source chemogenomic data-driven algorithms for predicting drug–target interactions

Abstract: While novel technologies such as high-throughput screening have advanced together with significant investment by pharmaceutical companies during the past decades, the success rate for drug development has not yet been improved prompting researchers looking for new strategies of drug discovery. Drug repositioning is a potential approach to solve this dilemma. However, experimental identification and validation of potential drug targets encoded by the human genome is both costly and time-consuming. Therefore, ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…To further confirm the value of our approach, we also used the mean percentile ranking (MPR), an evaluation index based on recall, to evaluate the performance of the algorithm. This evaluation index has been applied in recommendation algorithm and analyses of the performance for predicting drug-targets (Hu et al, 2008;Johnson, 2014;Li et al, 2015;Ding et al, 2017;Hao et al, 2019;Liu et al, 2019b;Liu et al, 2019c; and disease biomarkers (Chen et al, 2016;Zeng et al, 2016;Hong et al, 2019;Xu et al, 2019). For each disease, the genes were ranked in descending order according to the calculated gene-disease predictive value.…”
Section: Evaluation Indexes and Methodsmentioning
confidence: 99%
“…To further confirm the value of our approach, we also used the mean percentile ranking (MPR), an evaluation index based on recall, to evaluate the performance of the algorithm. This evaluation index has been applied in recommendation algorithm and analyses of the performance for predicting drug-targets (Hu et al, 2008;Johnson, 2014;Li et al, 2015;Ding et al, 2017;Hao et al, 2019;Liu et al, 2019b;Liu et al, 2019c; and disease biomarkers (Chen et al, 2016;Zeng et al, 2016;Hong et al, 2019;Xu et al, 2019). For each disease, the genes were ranked in descending order according to the calculated gene-disease predictive value.…”
Section: Evaluation Indexes and Methodsmentioning
confidence: 99%
“…The smaller the value, the better the prediction. More technical details about MPR can be found in [37, 38].…”
Section: Methodsmentioning
confidence: 99%
“…Drug-target relationships have far-reaching implications and are of central importance in drug repurposing [32] and drug design research in general. [33] It was found that both databases have a comparable number of drug-target relationships: 27,900 in ChEMBL and 27,613 in DrugBank.…”
Section: Enrichment Of Drug-target Pairsmentioning
confidence: 99%